SINKRONISASI HUKUM UNTUK ALIH FUNGSI LAHAN DALAM PENGEMBANGAN WISATA ALAM - Gibran Muhammad Gaza Palestin; Putri Nur Fazriyah; Endang Sutrisno; Mohammad Sigit Gunawan; Harmono (Faculty of Law, Universitas Pekalongan, 2025)
Land use conversion in the context of tourism development particularly nature-based tourism constitutes a strategic issue encompassing legal, environmental, and socio-economic dimensions. This study aims to analyze the extent to which Indonesia’s legal and regulatory frameworks have accommodated the governance of land-use conversion within the framework of sustainable tourism development. The research employs a normative juridical approach by examining statutory regulations relating to spatial planning and land-use conversion. This study is particularly relevant given the increasing strategic importance of environmental policies, including those in Kuningan Regency. One such regulation is Law Number 26 of 2007 concerning Spatial Planning. The findings indicate that, normatively, there is a degree of legal synchronization across various regulations that ensures conformity in spatial utilization with the Regional Spatial Plan (RTRW) and the Detailed Spatial Plan (RDTR), while also incorporating sustainability and environmental protection considerations. Nonetheless, practical challenges persist, including overlapping authorities, weak enforcement mechanisms, and limited public participation. Therefore, there is a pressing need to strengthen both legal structures and the legal culture of society to realize legal certainty and effective protection in land-use conversion for equitable and sustainable tourism development.